ANTI INFLAMMATORY ACTIVITY OF SUNGKAI LEAVES (Peronema canescens JACK) ETHANOL EXTRACT IN CARRAGEENAN INDUCED MICE - Madyawati Latief; Anggun Tri Fisesa; Putri Maya Sari; Indra Lasmana Tarigan (Jurnal Farmasi Sains dan Praktis, 2021)
Anti-inflammatory compounds play a role by inhibiting the formation of prostaglandin mediators, inhibiting the migration of leukocytes to the area of ​​inflammation, and inhibiting the release of prostaglandins from the cells where they are located. Several plant-derived compounds that can act as anti-inflammatory candidates are flavonoids, saponins, alkaloids, and phenols. This study aims to determine the anti-inflammatory activity of the ethanol extract of Sungkai leaves and to determine the effect of the concentration given on the level of anti-inflammatory activity. The method used was the formation of granuloma pockets and edema on the mice's backs by inducing subcutaneous carrageenan using ethanol extract of Sungkai leaves with various concentrations of 5%, 10%, and 15%, respectively. The results of anti-inflammatory activity showed that the ethanol extract of Sungkai leaves had a significant effect on the average exudate volume and the percentage of inflammation inhibition. At a concentration of 15%, the extract was able to reduce the volume of exudate by 46,67 ± 5,506 µl and inhibition of inflammation by 87.78%. In addition, the ethanol extract of Sungkai leaves significantly affected lymphocytes, stem neutrophils, and segment neutrophils, but did not significantly affect the number of monocyte cells. At a concentration of 15%, the ethanol extract of Sungkai leaves showed the smallest number of leukocyte cell types, namely 50.11 ± 2.389 lymphocyte cells; stem neutrophil cells 10,44 ± 0,475; segmented neutrophil cells were 19.78 ± 0.596 and monocyte cells 2,0 ± 0,236. It can be concluded that the ethanol extract of Sungkai leaves has anti-inflammatory activity but has not approached the effect of anti-inflammatory drugs in general.